Pengaruh Akuntabilitas, Transparansi dan Partisipasi Masyarakat terhadap Efektivitas Pengelolaan Alokasi Dana Desa - Ely Regina; Jawoto Nusantoro; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2026)
The purpose of this study was to determine the effect of accountability, transparency, and community participation on the effectiveness of village fund allocation management. This study is a quantitative study, with a sample of 100 respondents consisting of the Pagar Gading Village community. The research analysis method was carried out using multiple linear regression. The results of the study indicate that the variables of accountability, transparency, and participation simultaneously have a significant effect on the variable of affectivity in managing village fund allocations, as evidenced by the calculated F value > F table, namely 149.273 > 2.97. Accountability has a significant effect on the effectiveness of village fund management, as evidenced by the calculated T value > T table, namely 2.948 > 1.660. Transparency has a significant effect on the effectiveness of village fund management, as evidenced by the calculated T value > T table, namely 19.302 > 1.660. Participation has a significant effect on the effectiveness of village fund management, as evidenced by the calculated T value > T table, namely 4.333 > 1.660.